OS USOS DE SI E O DEBATE DE NORMAS DOS TRABALHADORES DE UMA INDÚSTRIA METAL-MECÂNICA | The self use and the debate of norms of workers from a Metal-Mechanic Industry (Trabalho & Educação, 2018)
This article has as object the analysis of complexity of working conditions of workers the production department of a metalworking industry located in the interior of Minas Gerais. Front a scenario profound changes in the working world, these professionals require to use practical knowledge and/or (re) normalizing the works prewrite in order to eke out the deficiencies and fill in the gaps of previous norms, as well as make use of you by yourself and others. Because of this, the study has as theoretical support ergological approach to Schwartz once it studies the work from the concrete activity of the workers. Therefore, the methodology applied in the case study as the research focuses in a specific organization and the relevance of studying the humans phenomena in your social relationship. The collection and analysis of data will be structured through semi structured observations the conditions and mode of production of work and semi structured interviews with ten workers.___Este artigo possui como objeto a análise da complexidade das situações de trabalho dos operários do setor de produção de uma indústria metal-mecânica localizada no interior de Minas Gerais. Diante de um cenário de profundas transformações no mundo trabalho, esses profissionais necessitam utilizar seus saberes práticos e/ou debaterem as tarefas prescritas a fim de suprir as deficiências e preencher as lacunas das normas antecedentes, bem como fazer usos de si por si e pelos outros. Por esse motivo, o estudo baseia-se na abordagem ergológica de Schwartz uma vez que estuda o trabalho a partir da atividade concreta de quem trabalha. Para tanto, a metodologia utilizada é o estudo de caso visto que a pesquisa concentra-se em uma organização específica e pela relevância de estudar os fenômenos humanos em suas relações sociais. A coleta e análise de dados foram realizadas por meio de observações sistemáticas das condições e do modo de produção de trabalho de um grupo constituído por dez trabalhadores.